2011
DOI: 10.1128/aac.00976-10
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Approaches to the Prevention and Treatment of HIV-1 Infection

Abstract: The discovery of the human immunodeficiency virus type 1 (HIV-1) in 1982 soon led to the identification and development of antiviral compounds to be used in treatment strategies for infected patients. Early in the epidemic, drug monotherapies frequently led to treatment failures because the virus quickly developed resistance to the single drug. Following the advent of highly active antiretroviral therapy (HAART) in 1995, dramatic improvements in HIV-1-infected patient health and survival were realized as more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 98 publications
3
66
0
Order By: Relevance
“…More interestingly, the model demonstrated that high synergistic inhibition of HCV replication can be achieved by combinatorial targeting of two downstream enzymes in the sterol pathway, revealing a potential strategy for HCV therapy. As demonstrated by the HCV study, combinatorial drug therapy is an approach increasingly used to overcome viral drug resistance by targeting multiple factors or pathways necessary for infection (38). For the treatment of many viruses, including HIV, HCV and Influenza, combinatorial drug administration has shown increased and broadened efficacy (38)(39)(40).…”
Section: Systems Approaches To Design and Evaluate Anti-viral Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, the model demonstrated that high synergistic inhibition of HCV replication can be achieved by combinatorial targeting of two downstream enzymes in the sterol pathway, revealing a potential strategy for HCV therapy. As demonstrated by the HCV study, combinatorial drug therapy is an approach increasingly used to overcome viral drug resistance by targeting multiple factors or pathways necessary for infection (38). For the treatment of many viruses, including HIV, HCV and Influenza, combinatorial drug administration has shown increased and broadened efficacy (38)(39)(40).…”
Section: Systems Approaches To Design and Evaluate Anti-viral Therapiesmentioning
confidence: 99%
“…As demonstrated by the HCV study, combinatorial drug therapy is an approach increasingly used to overcome viral drug resistance by targeting multiple factors or pathways necessary for infection (38). For the treatment of many viruses, including HIV, HCV and Influenza, combinatorial drug administration has shown increased and broadened efficacy (38)(39)(40). However, not all drugs can be combined in an effective way without increased toxicity, and therefore investigations into the combined effects of two or more anti-viral drugs are especially significant.…”
Section: Systems Approaches To Design and Evaluate Anti-viral Therapiesmentioning
confidence: 99%
“…18 Therefore, the combinatorial approach should be taken into consideration when designing future microbicide studies. Some novel studies have examined the efficacy of ARV combinations as microbicides.…”
Section: Introductionmentioning
confidence: 99%
“…18 Additionally, a reduction in the amounts of ARVs used in vivo may result in a reduction of adverse effects, limiting the local injuries, the toxicity, and the inflammation caused by local microbicide application before sexual intercourse.…”
mentioning
confidence: 99%
“…These findings suggest that a single-component microbicide based on VRC01 or any other bnMAb may fail to provide sufficient protection and could even lead to the accumulation of resistant strains in circulating virus populations. In practice, a combinatorial strategy will have to be implemented for any microbicide candidates, as has been the case in the treatment of HIV-1-infected patients (22). Thus, analysis of VRC01's potential for synergy with other microbicide candidates would provide valuable information toward the bnMAb's potential as a component of combination microbicides.…”
mentioning
confidence: 99%